Discurso hegemónico y representaciones sociales : casuística indígena en la prensa digital colombiana - Merchán Cante, Harvey Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: This thesis analyzes some of the ways in which unequal power relationships are represented in the Colombian digital press. Content analysis was performed based on critical discourse theory, taking as a focus national news in their digital format in Colombia during the years 2010 to 2018. In order to evaluate the presence of different hegemonic discourses in different online media, a coding scheme was developed based on a combination of conceptual tools proposed by Teun Van Dijk, Antonio Gramsci and others. Through a quantitative and qualitative study, the objectives of interpreting and unveiling the way in which the digital press determines strategies of legitimization of actions over the indigenous movements in Colombia, as well as deepening about the linguistic and discursive strategies that predominate in respect to the indigenous movements in Colombia. On the other hand, it was determined the characteristics of the hegemony discourse about indigenous movements in the Colombian digital press, analyzing the discursive strategies used in the digital media to legitimize and delegitimize the different indigenous movements in Colombia and thus finally, concluding about how the discursive strategies of the Legitimization and Delegitimization create social representations in the digital press in Colombia.